INTELLECTUAL PROPERTY RIGHTS LAW CHALLENGES IN NEW NORMAL ERA - Ida Nadirah (Proceeding International Seminar of Islamic Studies, 2021)
The global world is currently facing a very difficult period due to the outbreak of the SARS-CoV-2 coronavirus pandemic or commonly known as covid 19. Several aspects of community life such as economy, education and health have decreased because all human activities are limited and they carry out more activities in house. Indonesia must be ready to face the challenges of this situation by preparing Intellectual Property Rights Law which can fulfill the interests of all Indonesian people. This juridical normative research is sourced from secondary data or library data that comes from online and offline library materials. In the current era of digitalization, intellectual property rights are a creative industry that is very fundamental in driving economic growth. Intellectual Property Rights are resources that are based on the intellectual ability of a person which is then manifested in the form of creative works in the fields of science, art and technology. There are many challenges that will be faced in the application of intellectual property rights in this digitalization and new normal era because of the different characteristics of Indonesian people who are not yet literate in Intellectual Property Rights Law. The government and stakeholders need to carry out reforms and socialization of intellectual property rights law, especially in the field of copyright and trademark rights that are in accordance with the culture of the Indonesian people to encourage economic development in this new normal era. Keywords: Challenges, Inteletual Property Rights, New Normal